Rapid characterization of the chemical constituents and rat metabolites of the Wen‐Jing decoction by ultra high performance liquid chromatography coupled with electrospray ionization quadrupole time‐of‐flight tandem mass spectrometry. Issue 6 (7th February 2019) - Xu, Liu; Li, Moying; Zhou, Haifeng; Zhang, Bei; Zhang, Zhiqiang; Han, Nina; Wu, Tong
Abstract: The Wen‐Jing decoction, a traditional Chinese medicine formula, has been used as a blood‐activating and stasis‐eliminating drug to treat gynaecological syndromes, such as dysmenorrhea, amenorrhea, and menstrual disorders. However, its pharmacodynamic material basis and mechanism of action have not been thoroughly elucidated to date. The goal of this study was to characterize and identify multiple constituents and metabolites in Wen‐Jing decoction. An ultra high performance liquid chromatography coupled with electrospray ionization quadrupole time‐of‐flight tandem mass spectrometry method was established and validated in the present study for the first time. A total of 101 compounds, including 11 monoterpene glycosides, 19 flavonoids, 49 triterpene saponins, 5 phthalides, 3 phytoecdysones, and 14 others, were unambiguously or tentatively characterized by comparing their retention times and MS data with reference standards or with data reported in the literature. After oral administration of Wen‐Jing decoction, 27 compounds, including nine prototype compounds and 18 metabolites were detected in rat plasma. Thus, the ultra high performance liquid chromatography coupled with electrospray ionization quadrupole time‐of‐flight tandem mass spectrometry method was found to be efficient for in‐depth structural elucidation of chemical compounds in complex matrices of herbal medicines, which will provide useful chemical information for quality control and mechanism‐of‐action research.